Bone Cancer Detection Using Feature Extraction Based Machine Learning Model. (20th December 2021) - Sharma, Ashish; Yadav, Dhirendra P.; Garg, Hitendra; Kumar, Mukesh; Sharma, Bhisham; Koundal, Deepika
Abstract : Bone cancer is considered a serious health problem, and, in many cases, it causes patient death. The X-ray, MRI, or CT-scan image is used by doctors to identify bone cancer. The manual process is time-consuming and required expertise in that field. Therefore, it is necessary to develop an automated system to classify and identify the cancerous bone and the healthy bone. The texture of a cancer bone is different compared to a healthy bone in the affected region. But in the dataset, several images of cancer and healthy bone are having similar morphological characteristics. This makes it difficult to categorize them. To tackle this problem, we first find the best suitable edge detection algorithm after that two feature sets one with hog and another without hog are prepared. To test the efficiency of these feature sets, two machine learning models, support vector machine (SVM) and the Random forest, are utilized. The features set with hog perform considerably better on these models. Also, the SVM model trained with hog feature set provides an F 1 -score of 0.92 better than Random forest F 1 -score 0.77.